Oxidative Stress in Oral Diseases: Understanding Its Relation with Other Systemic Diseases - Kumar, Jaya; Teoh, Seong Lin; Das, Srijit; Mahakknaukrauh, Pasuk (Frontiers in Physiology, 2017)
Oxidative stress occurs in diabetes, various cancers, liver diseases, stroke, rheumatoid arthritis, chronic inflammation and other degenerative diseases related to the nervous system. The free radicals have deleterious effect on various organs of the body. This is due to lipid peroxidation and irreversible protein modification that leads to cellular apoptosis or programmed cell death. During recent years, there is a rise in the oral diseases related to oxidative stress. Oxidative stress in oral disease is related to other systemic diseases in the body such as periodontitis, cardiovascular, pancreatic, gastric and liver diseases. In the present review, we discuss the various pathways that mediate oxidative cellular damage. Numerous pathways mediate oxidative cellular damage and these include caspase pathway, PERK/NRF2 pathway, NADPH oxidase 4 pathways and JNK/mitogen-activated protein (MAP) kinase pathway. We also discuss the role of inflammatory markers, lipid peroxidation and role of oxygen species linked to oxidative stress. Knowledge of different pathways, role of inflammatory markers, and importance of low-density lipoprotein, fibrinogen, creatinine, nitric oxide, nitrates and highly sensitive C-reactive proteins may be helpful in understanding the pathogenesis and plan better treatment for oral diseases which involve oxidative stress.